Old views and new insights: taxonomic revision of the Bukovina blind mole rat, Spalax graecus (Rodentia: Spalacinae). (29th October 2013) - Németh, Attila; Homonnay, Zalán G.; Krízsik, Virág; Csorba, Máté; Pavlíček, Tomáš; Hegyeli, Zsolt; Hadid, Yarin; Sugár, Szilárd; Farkas, János; Csorba, Gábor
<x xml:space="preserve">Abstract</x> As a result of their rather uniform external appearance and gross cranial morphology, the systematics of blind mole rats has been hotly debated over the last century; however, the separation of the large‐bodied and small‐bodied blind mole rats at the genus level (Spalax and Nannospalax, respectively), suggested earlier on morphological grounds, is strongly supported by recent molecular biological evidence. The species of Spalax have so far been distinguished from each other by cranial traits only, especially the outline of sutures of the cranium, and the shape and relative size of the nasal and parietal bones. Based on mitochondrial DNA sequences (with the widest taxonomic and geographic coverage so far) and detailed anatomical comparisons of museum specimens, we herewith provide a revision of the taxonomic and phylogenetic status of the westernmost representative of the genus, Spalax graecus s.l. We clarify that antiquus and istricus – presently regarded as synonyms of graecus – are well‐defined species, and they together form a separate clade within Spalax. The robustness of our conclusions is supported by the combined evidence of morphology, multilocus phylogeny, species distribution, and taxon history (species congruence with past tectonic and climate events). © 2013 The Linnean Society of London